'Trouble at the gates': Italian base workers and foreign relations at Camp Darby, 1968-1971. (2nd November 2019) - Wilson, Holly
ABSTRACT: From 1968 to 1971, close to a thousand Italian civilian employees at the United States (U.S.) military base, Camp Darby, located in Tuscany faced a series of recurrent layoffs from the U.S. Department of Defence. In a determined effort to protect their jobs, the base workers launched a series of disruptive and persistent forms of protest and civil disobedience that played on the instability of the Italian government and threatened to unsettle the relations between Italy and the United States. Drawing on original archival material from both countries, including large numbers of Italian-language sources, this article provides the first detailed examination of the labor dispute at Camp Darby. I will argue that the base workers secured the intervention of politicians, diplomats, and the Prime Minister in the resolution of the labor dispute by asserting the political significance of their cause both domestically and internationally. The result, I argue, was foreign relations shaped by the agency and often, individual agenda of the non-American workforce at Camp Darby. The dispute points to the complex encounters at play on U.S. military bases abroad as American foreign relations are faced with the convergence of radical labor traditions with Italian domestic politics, and U.S. labor expectations.